Influences on the thermal efficiency of energy piles. (15th March 2015) - Cecinato, Francesco; Loveridge, Fleur A.
Abstract: Energy piles have recently emerged as a viable alternative to borehole heat exchangers, but their energy efficiency has so far seen little research. In this work, a finite element numerical model is developed for the accurate 3D analysis of transient diffusive and convective heat exchange phenomena taking place in geothermal structures. The model is validated by reproducing both the outcome of a thermal response test carried out on a test pile, and the average response of the linear heat source analytical solution. Then, the model is employed to carry out a parametric analysis to identify the key factors in maximising the pile energy efficiency. It is shown that the most influential design parameter is the number of pipes, which can be more conveniently increased, within a reasonable range, compared to increasing the pile dimensions. The influence of changing pile length, concrete conductivity, pile diameter and concrete cover are also discussed in light of their energetic implications. Counter to engineering intuition, the fluid flowrate does not emerge as important in energy efficiency, provided it is sufficient to ensure turbulent flow. The model presented in this paper can be easily adapted to the detailed study of other types of geothermal structures. Highlights: A numerical model for 3D thermal transient analysis of energy piles is developed. The model is validated against both field data and an analytical solution. Key parameters are then identified for efficient thermal design of energy piles. Energy efficiency is maximised by large pipe number and concrete conductivity. Large exchanger fluid velocity does not have a major impact on efficiency.